The enactment of teacher leadership in a township high school : a restricted form - Mancoko, Melikhaya Kenneth (Rhodes University, Faculty of Education, Department of Education, 2015)
Whilst the concept of teacher leadership is not new in the international literature (Grant, 2006), research on the topic of teacher leadership is emerging slowly as a new area of research interest in South Africa (Grant, 2006; Grant, 2005; Singh, 2007). Teacher leadership is basically about teachers who are leaders within and outside the classroom, who identify with and contribute to a community of teacher learners and leaders, influence others to improve their teaching practice and accept responsibility for realising the goals of their organisation (Katzenmeyer & Moller, 2001 in Grant, 2006). Therefore, teachers' roles in operating as leaders in schools are acknowledged in literature. This study is a replication of a University of KwaZulu-Natal multi-case study on the enactment of teacher leadership conducted in various educational institutions in the province of KwaZulu-Natal. In line with the original study, this study aimed at obtaining an understanding of the enactment of teacher leadership in a township high school in the King William's Town education district, in the Eastern Cape. I further explored what factors promoted or hindered such enactment. As an Eastern Cape Master of Education student participating in a group research programme at Rhodes University, we adopted and used the same research questions, research approach, data collection methods as well as data analysis techniques as utilised in the original study. Therefore, this research study was conducted within the interpretive paradigm, following a qualitative approach. I adopted a case study methodology, with the case being the school and three teacher leaders as units of analysis. Data were gathered through a multi-method approach which consisted of a school profile, a focus group interview, semi-structured individual interviews, questionnaires, self reflective journaling and observations. Whilst the research was guided by distributed leadership theory, Grant's (2008) Model of teacher leadership and thematic content analysis was used to analyse data. Research findings revealed that the enactment of teacher leadership was evident in Zones 1, 2 and 4 of Grant's (2008) Model of teacher leadership in the case study school. However, a restricted form of teacher leadership was enacted in Zone 3, whereby teachers were not regularly involved in school-wide decision-making processes. When teacher leadership was enacted, it was in a form of authorised distributed leadership. The study further identified the autocratic leadership style of the principal and of the School Management Team members, as well as the non-inclusive school culture as main barriers towards the enactment of teacher leadership in the case study school. Despite these barriers, teachers' high levels of enthusiasm were identified as an enabling factor that promoted the enactment of teacher leadership in the case study school.
Keywords: Educational leadership -- South Africa -- King William's Town; Teacher participation in administration -- South Africa -- King William's Town; School management and organization -- South Africa -- King William's Town; Education, Secondary -- South Africa -- King William's Town